1987
DOI: 10.1038/clpt.1987.132
|View full text |Cite
|
Sign up to set email alerts
|

Trazodone kinetics: Effect of age, gender, and obesity

Abstract: Single 25 mg intravenous and 50 mg oral doses of trazodone were given to 43 healthy subjects, divided into young men and women (aged 18 to 40 years) and elderly men and women (aged 60 to 76 years). Among men, trazodone volume of distribution (Varea) was increased in elderly vs. young subjects (1.15 vs. 0.89 L/kg; P less than 0.05), and clearance decreased (1.65 vs. 2.31 ml/min/kg; P less than 0.05), thereby increasing elimination half-life (t1/2) in elderly men (8.2 vs. 4.7 hours; P less than 0.001). Varea in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 14 publications
4
51
1
1
Order By: Relevance
“…For midazolam, no difference in bioavailability was found between normal-weight volunteers (66 ± 2 kg, n = 20) and obese volunteers (117 ± 8 kg, n = 20) (40 ± 3% versus 42 ± 4%, P > 0.05, respectively), nor was a difference found in time of maximum concentration (T max ) or maximum concentration (C max ) itself (81). Similarly, no difference in bioavailability or oral absorption rate was found for trazodone, cyclosporine, dexfenfluramine, and moxifloxacin between obese and nonobese subjects (82)(83)(84)(85).…”
Section: The Influence Of Obesity On Oral Bioavailability and Absorptcontrasting
confidence: 48%
See 1 more Smart Citation
“…For midazolam, no difference in bioavailability was found between normal-weight volunteers (66 ± 2 kg, n = 20) and obese volunteers (117 ± 8 kg, n = 20) (40 ± 3% versus 42 ± 4%, P > 0.05, respectively), nor was a difference found in time of maximum concentration (T max ) or maximum concentration (C max ) itself (81). Similarly, no difference in bioavailability or oral absorption rate was found for trazodone, cyclosporine, dexfenfluramine, and moxifloxacin between obese and nonobese subjects (82)(83)(84)(85).…”
Section: The Influence Of Obesity On Oral Bioavailability and Absorptcontrasting
confidence: 48%
“…Only six studies have directly compared the oral bioavailability and absorption rate of drugs between obese and nonobese subjects on the basis of both oral and intravenous administration (80)(81)(82)(83)(84)(85). For propranolol, clearance (CL) after an intravenous dose was not different between six obese (136 ± 36 kg) and six control (67 ± 5 kg) subjects.…”
Section: The Influence Of Obesity On Oral Bioavailability and Absorptmentioning
confidence: 99%
“…Studies on amitriptyline [4,18,28,31,33,34,54,55], carbamazepine [28,30,31,36,37], tramadol [22,46,[56][57][58][59] and trazodone [47][48][49][60][61][62][63] related deaths and PMR have frequently been reported. Propofol related deaths [64][65][66][67][68][69] have frequently been reported, but studies on PMR of propofol have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…dose of trazodone identified that women had a higher distribution volume irrespective of age. Also, clearance was unaffected by age in women but not in men and elimination half-life was longer in young women than in young men, but shorter in elderly women than in elderly men [125].…”
Section: Trazodonementioning
confidence: 98%